Research on the Process of Ni60 Laser Cladding for Surface Strengthening of Nonmagnetic Drilling Tools - LIU Lilan; LI Sicong; YANG Fan; HAN feiyan; WU Ziying (工程科学与技术)
ObjectiveThe material of nonmagnetic drilling tools is 316L stainless steel. When operating underground, nonmagnetic drilling tools are prone to wear and corrosion due to the poor wear and corrosion resistance of 316L stainless steel. Cladding a carbide alloy on the surface of nonmagnetic drilling tools serves as an effective method to enhance their wear and corrosion resistance. Ni60 alloy exhibits high hardness and wear resistance; however, it also presents high crack sensitivity, which seriously restricts its engineering application. This study aims to determine the optimal process parameters for preparing crack-free Ni60 alloy coatings on 316L stainless steel substrates to strengthen the surface of nonmagnetic drilling tools.MethodsLaser coaxial powder feeding technology was utilized to clad Ni60 alloy powder on the surface of 316L stainless steel. The process parameters, such as laser power, scanning speed, and powder feeding rate, were considered as influencing factors. First, orthogonal experiments of single-layer single-pass laser cladding were conducted. Sixteen sets of single-layer single-pass cladding layers were obtained, and penetration testing was employed to detect cracks in the cladding layers. An inverted metallographic microscope was then utilized to observe the microstructures of the cross-sections of the cladding layers, and a Vickers hardness tester was utilized to measure the microhardness of the cladding layers. The melting height, melting depth, and melting width of the 16 sets of single-layer single-pass cladding layers were measured to calculate the crack density, dilution rate, and forming coefficient. Some cladding layers with no cracks and a low dilution rate were selected from the 16 sets. Next, taking microhardness, dilution rate, and forming coefficient as quality indicators, a comprehensive weighted scoring method was proposed to select three sets of cladding layers with the highest scores. The process parameters of the selected three sets of single-layer single-pass cladding layers were then utilized to conduct single-layer multi-pass cladding tests with a 50% overlap rate. The microhardnesses and microstructures of the single-layer multi-pass cladding layers were measured. Based on the thickness, microstructure, and microhardness of the single-layer multi-channel cladding layers, the process parameters that met the requirements of the coatings for the nonmagnetic drilling tool considered were finally determined.Results and DiscussionsIn the results of the single-layer single-pass cladding experiments, crack defects were found in the cladding layers of A2, A3, A4, A7, A8, and A10. The laser energy analysis showed that their line energy and mass energy were low, which led to incomplete melting of the alloy powder and also caused the microstructures of the layers to be uneven. In addition, the cladding layers of A15 and A16 were also eliminated because their dilution rates were too high. The remaining eight sets of cladding layers, which exhibited no cracks or pores in their cross-sections, were selected for further analysis. The hardness of the Ni60 alloy coating ranged from 528 to 788 HV, while the hardness of the substrate ranged from 205 to 232 HV. Taking microhardness, dilution rate, and forming coefficient as quality evaluation indicators, with high hardness, low dilution rate, and high forming coefficient considered optimal, the comprehensive weighted scores of the selected eight sets of single-layer single-pass cladding layers were calculated. The three sets of cladding layers with the highest scores were A5, A9, and A1, and their process parameters were utilized to conduct single-layer multi-channel experiments. Therefore, three sets of single-layer multi-channel cladding layers, numbered G1, G2, and G3, were obtained. The crack penetration testing showed that there were no cracks in the cladding layers. The thicknesses of the G1, G2, and G3 cladding layers gradually increased due to the corresponding increases in laser power and powder feeding rate. The dilution rate of the G1 cladding layer remained between 17.8% and 20.7%, that of G2 remained between 15.3% and 18.9%, and that of G3 remained between 7.6% and 9.0%. The microhardness of the Ni60 alloy coating ranged from 638 to 882 HV, and the hardness of the substrate ranged from 218 to 273 HV. The microstructures of the G1 and G2 cladding layers exhibited typical rapid solidification characteristics. From the bonding zone to the surface of the cladding layers, the microstructures showed a transition from continuous planar crystals and dendritic crystals to equiaxed crystals. This illustrated that the Ni60 alloy powder formed a dense metallurgical bond with the 316L stainless steel substrate. However, no obvious and continuous planar crystal layer was found in the bonding zone of the G3 cladding layer, which was attributed to the low dilution rate and uneven temperature variation.ConclusionsThe Ni60 alloy coating of the G2 cladding layer meets the requirements of a 2.0～2.5 mm thickness and a 55～60 HRC hardness for the nonmagnetic drilling tool. When the dilution rate is approximately 15%～20%, the microstructure of the single-layer multi-channel cladding layer exhibits good formation without cracks or pores. The transverse microhardness of the single-layer multi-channel Ni60 alloy coatings ranges from 588 to 889 HV. At the middle width of the single-layer multi-channel cladding layer, the longitudinal microhardness of the Ni60 alloy coating ranges from 638 to 882 HV, while the longitudinal microhardness of the 316L substrate ranges from 218 to 273 HV. The microhardness of the Ni60 alloy coating is approximately four times that of the 316L substrate. The optimal process parameters, determined through experiments and analysis, are as follows: laser power of 1 600 W, scanning speed of 3 mm/s, powder feeding rate of 0.6 r/min, and overlap rate of 50%.